2016
DOI: 10.15673/fst.v10i4.250
|View full text |Cite
|
Sign up to set email alerts
|

Development of formulation multicomponent protein-fat emulsion

Abstract: The article is based on research of the protein components of different nature analysis. The possibility of their use as components of protein and fat emulsions for the purpose of modeling their optimal formulations for use in the composition of meat pates was proved. Rational individuals’ emulsification process parameters, which guarantee high-quality homogeneous emulsions, were found. The samples of protein and fat emulsions using protein drugs and partial replacement of animal fats fortified blend of vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…A series of the conducted studies demonstrated that introduction of vitaminized blended vegetable oils in PFE favors the improvement of their main parameters of the functional properties, which data are presented in Table 4 [2]. The water-retaining ability (WRA) of PFE with «Belkoton А91» is in average by 9,0 % higher comparing with other proteins.…”
Section: Vitaminized Blended Vegetable Oilsmentioning
confidence: 96%
See 2 more Smart Citations
“…A series of the conducted studies demonstrated that introduction of vitaminized blended vegetable oils in PFE favors the improvement of their main parameters of the functional properties, which data are presented in Table 4 [2]. The water-retaining ability (WRA) of PFE with «Belkoton А91» is in average by 9,0 % higher comparing with other proteins.…”
Section: Vitaminized Blended Vegetable Oilsmentioning
confidence: 96%
“…The organoleptic assessment of paste masses with RFE, based on VBVO, testifies that their addition in pastes' recipes in amount 15...20 % doesn't worsen the taste, smell and doesn't influence the consistence of products [2].…”
Section: Vitaminized Blended Vegetable Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Сучасне виробництво продуктів харчування перейшло на новий щабель розвитку, коли продовольча програма повинна вирішувати проблему задоволення не тільки потреб населення в окремих харчових продуктах, а й забезпечувати їх збалансованість за основними нутрієнтами [11]. Тому, одним з перспективних напрямків досліджень є удосконалення технологій і розробка рецептур м'ясних паштетів з додаванням купажованих рослинних олій, збагачених жиророзчинними вітамінами або БЖЕ, створених на основі вітамінізованих купажованих рослинних олій і білків, з метою покращення збалансованості жирнокислотного та вітамінного складів, якісних характеристик готової продукції та підвищення засвоюваності, а також розширення асортименту [12][13][14][15][16][17].…”
Section: ____________________________________________________________...unclassified